Erratum: Perbandingan Jenis Pola Minum Terhadap Status Hidrasi Pada Remaja Laki-Laki Dan Perempuan - Grisna Febiyanti; Kunjung Ashadi (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.562 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.